Hubungan Organizational Citizenship Behavior (OCB), Komitmen Organisasi, Kepuasaan Kerja terhadap Kinerja Perawat Rawat Inap di RSUD Dr. Adjidarmo Kabupaten Lebak - Dennison Laurensius Mulya; Yohana F. Cahya Palupi Meilani (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
One indicator of the success of the healthcare industry, especially hospitals, is the level of employee performance. One of the performances that plays an important role is the performance of nurse services to patients, nurses have an obligation to provide medical and non-medical services to patients. Good performance reflects the performance of a hospital, so performance is important to be optimized so that the hospital's success rate is optimal. Organizational Citizenship Behavior (OCB) is an important aspect that every nurse needs to have to support effectiveness at work, the level of commitment to the organization is an aspect that plays a role for every nurse in supporting the achievement of hospital goals, and a high level of job satisfaction makes nurses provide the best service. Research data will be collected through a physical questionnaire which will be given to 100 inpatient nurses at RSUD Dr. Adjidarmo Lebak district. Data analysis used the Smart PLS application version 4.0.7.8 and the partial least square equation analysis method. There is a positive and significant effect between OCB, organizational commitment, and job satisfaction on the performance of inpatient nurses at RSUD Dr. Adjidarmo Lebak disctrit.